2015
DOI: 10.1051/matecconf/20152002002
|View full text |Cite
|
Sign up to set email alerts
|

Operational modal analysis with uncertainty quantification for SDDLV-based damage localization

Abstract: Abstract. The Stochastic Dynamic Damage Locating Vector (SDDLV) approach is a vibration-based damage localization method based on a finite element model of a structure in a reference state and output-only measurements in both reference and damaged states. A stress field is computed for loads in the null space of a surrogate of the change in the transfer matrix at the sensor positions, where the null space is obtained based on the identified modal parameters in both structural states. Then, the damage location … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…For instance, in (Pereira et al, 2020), modal parameter uncertainties identified in continuous dynamic monitoring were used to remove outliers during modal tracking. Döhler et al (2015) improved the results of a damage localization method by including the computed uncertainty levels in modal parameters. Verboven et al (2004) performed an EMA test, finding that the mathematical modes had a much higher level of uncertainty than the physical modes.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, in (Pereira et al, 2020), modal parameter uncertainties identified in continuous dynamic monitoring were used to remove outliers during modal tracking. Döhler et al (2015) improved the results of a damage localization method by including the computed uncertainty levels in modal parameters. Verboven et al (2004) performed an EMA test, finding that the mathematical modes had a much higher level of uncertainty than the physical modes.…”
Section: Introductionmentioning
confidence: 99%